Imposex in Cantharus viverratus from São Vicente Island (Cabo Verde) - Santos, Ruy Miguel Alfama Lopes dos (2018)
Tributyltin (TBT) compounds were biocide agents widely used in antifouling systems since the 60s. However, their high toxicity over non-target organisms led to a progressive restriction of their use, culminating into their global ban by 2008. The extensive use of these compounds in years prior to the ban led to their build up in the sediment compartment of coastal areas around the world. This fact, together with their possible continued use in countries without regulatory supervision, justifies the need to perform regular TBT pollution monitoring. The imposex (superimposition of male characters onto female of prosobranch gastropods), which is caused by TBT exposure, is an effective biomarker to assess environmental TBT pollution levels. Imposex is already reported for more than 260 species of gastropods around the world, but there is an astonishing lack of information regarding the occurrence of this phenomenon in the west coast of Africa. There is also no information about suitable bioindicator species for this region, which constitutes a serious setback, not only for the countries in the region, as for the global effort to implement regulatory policies and monitor their effectiveness. Therefore, the present work aimed to propose for the first time a suitable bioindicator species that can be used for monitoring biological effects of TBT pollution in the western African coast and use it to make the first assessment of TBT pollution in the São Vicente island, where is located the main harbour of the Republic of Cabo Verde. Because of its widespread distribution area, from the Canary islands and the Cabo Verde Archipelago to Angola, its abundance and apparent TBT sensibility, the species Cantharus viverratus (Kiener, 1834) was selected as a potential candidate to monitor the biological effects of TBT pollution through the imposex response. Adult C. viverratus were collected between August and October 2012 along the coast of São Vicente island and the morphological expression of imposex was assessed and compared to general VDS (vas deferens sequence) schemes available for other bioindicators. An updated VDS scheme that faithfully describe the morphological expression of imposex in C. viverratus was therefore determined, including seven levels of female virilization (from stage 0 to 6), following at least three different evolution pathways (a, b and c). After the new VDS scheme was established, the assessment of imposex levels was performed through the estimation of the percentage of females affected with imposex (%I),the mean female penis length (FPL), the relative penis length index (RPLI), the vas deferens sequence index (VDSI) and the percentage of sterilized females (%S). The organotin body burden was also determined at 6 sampling stations, revealing a positive relation with the imposex levels registered. Females affected with imposex were only found at sites under the São Vicente's harbour influence, exhibiting values as high as VDSI≥5 at hotspots inside this harbour. The results revealed that the São Vicente harbour is the focus of TBT pollution in the island due to the occurrence of high naval traffic and shipyard activities, and possibly to the TBT release from sediments as a consequence of historical contamination by this compound.